Protocol for inoculum production and inoculation of maize with E. turcicum for resistance screening of pathogen - CGIAR Research Program on Maize (2021)
he identification of NCLB resistant lines in this study has set the premise for development of NCLB resistant hybrids for WCA as well as the improvement of tropical maize breeding populations for NCLB resistance.